Process variation tolerant SRAM array for ultra low voltage applications - Kulkarni, Jaydeep P.; Kim, Keejong; Park, Sang Phill; Roy, Kaushik (2008 45th ACM/IEEE Design Automation Conference, 2008)
In this work, we propose a Schmitt Trigger (ST) based differential sensing SRAM bitcell that can operate at ultra-low supply voltage. The proposed Schmitt Trigger SRAM cell addresses the fundamental conflicting design requirement of read versus write operation of a conventional 6T cell. Schmitt Trigger operation gives better read-stability and as well as better writeability compared to the standard 6T cell. The proposed ST bitcell incorporates a built-in feedback mechanism, achieving process variation tolerance - a must for future nano-scaled technology nodes. Measurements on 10 test-chips fabricated in 130nm technology show that the proposed Schmitt Trigger bitcell gives 58% higher read Static Noise Margin (SNM), 2X higher writetrip-point and 120mV lower read Vmin compared to the conventional 6T cell. The ST SRAM array is operational at 150mV of supply voltage.